GOOD PRACTICES FOR MAINTAINING DIVERSITY OF TROPICAL FRUIT TREES THROUGH VALUE ADDITION ACTIVITIES BY WOMAN FARMERS IN EAST JAVA - Kuntoro Boga Andri (Socio-Economics/Agribusiness Department, 2016)
The tropical fruits genetic resources, had a vital roles on nourish and source of income of local people as well as natural preservation. The study which was conducted at two sites in East Java Province, Indonesia during 2011 to 2012, aim to describe the significane of empowering women group to improve processing and market local mangos and citrus products. The study have proved the income contribution from mango and citrus production and its derivatives in both sited may reach 51 and 55 percent of total family income. To overcome of cheap price of fruits in the harvest season and enhance processing activities, training on processing techniques of mango was carried out by research institute (AIAT) in cooperation with NGO for the women farmers groups. In both sites, the processing units use all local varieties of fruits from the home garden and forest. Products currently are just sold in the local markets. Market expansion with an efficient distribution process in the future through promotion efforts may increase total consumers demand and marketing area. The practiced have maintaining diversity of tropical fruit trees through empowered women group to get the value added from local varieties of mango and citrus by process product and group marketing.